WHAT ABOUT LIQUIDITY?: AN UNDEREXPLORED FACTOR TO BE TAKEN INTO ACCOUNT IN ECUADORIAN BUSINESS MANAGEMENT. - Hidalgo Cañizares, Claudia (2017)
The present study explores the concept of liquidity and how liquidity ratios can be employed depending on each company´s needs and characteristics. Numerous authors were analyzed, which described years back the first concepts of liquidity, its usefulness and importance. The paper also mentions the best ways to measure it, and the liquidity ratios preferred by most authors, such as working capital which measures a company´s efficiency and current financial health. A section of the paper describes the different determinants of liquidity such as size and age, and how these affect companies, especially in developing countries. Furthermore, there is a thorough analysis regarding profitability, and how these important aspects of a company are interrelated. Many authors describe a trade-off, given that a key factor that determines a company’s profitability is its level of liquidity, but there must be an appropriate balance. The study points out the negative effects that poor liquidity management can cause –by having too much or too little liquid assets- such as excessive bank loans and overdraft fees, or, on the other hand high maintenance costs and low investments, which directly affect a company’s profitability, and how this is more common in developing countries. Moreover, alternative ways of financing are described, which can be convenient substitutes for companies that don’t have a large amounts of assets and strong structures they can rely on, plus limited access to bank loans. These include factoring and collateral, which tend to be least used in developing countries including Ecuador.